2008
DOI: 10.1148/radiol.2463070486
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor MR Imaging of Cortical Lesions in Multiple Sclerosis: Initial Findings

Abstract: DIR and PSIR combined with nonlinear image registration allowed direct focal measurement of FA and MD in cortical lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
4
38
1
1
Order By: Relevance
“…These results are similar to others presented earlier (Cifelli et al, 2002; Fabiano et al, 2003; Inglese et al, 2004; Poonawalla et al, 2008; Dineen et al, 2009; Roosendaal et al, 2009; Raz et al, 2010; Kern et al, 2011; Yu et al, 2012). However it is important to point out that we also found a signature of extensive demyelination in the normal appearing white matter, which was only rarely described in former diffusion tensor imaging studies.…”
Section: Discussionsupporting
confidence: 92%
“…These results are similar to others presented earlier (Cifelli et al, 2002; Fabiano et al, 2003; Inglese et al, 2004; Poonawalla et al, 2008; Dineen et al, 2009; Roosendaal et al, 2009; Raz et al, 2010; Kern et al, 2011; Yu et al, 2012). However it is important to point out that we also found a signature of extensive demyelination in the normal appearing white matter, which was only rarely described in former diffusion tensor imaging studies.…”
Section: Discussionsupporting
confidence: 92%
“…4,21 This increase of FA has been attributed to the specific characteristics of cortical lesions within the examined GM. Cortical lesions are characterized by low inflammatory demyelination, microglia proliferation and activation as well as loss of dendritic arborization 22 distinguishing them from WM lesions.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Poonawalla et al ( 86 ) found increased FA values in intracortical MS lesions, which might refl ect increased tissue structural coherence due to reduced dendritic arborization, or increased activation of microglia with extended processes that sheathe neuronal cell bodies and dendrites.…”
Section: Diffusion-tensor Mr Imagingmentioning
confidence: 99%